2004
DOI: 10.1002/jcla.20025
|View full text |Cite
|
Sign up to set email alerts
|

Sero epidemiology of Bordetella pertussis immune responses in a healthy population in northern Greece

Abstract: A seroepidemiological study was conducted on a representative sample of the northern Greek population (healthy individuals, age range=1 day to 80 years) to assess the prevalence of antibodies to pertussis toxin (PT) and filamentous hemagglutinin (FHA). Antibody concentrations were significantly elevated with age (analysis of variance (ANOVA), P<0.001). In addition, a significant increase in antibody levels was detected in subjects >50 years old compared to children aged 5-10 years (post-hoc Scheffe analysis, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…In the age groups up to 19 years, the percentage of samples with high titres remained stable at 5–7·9%, reflecting natural boosting and limited vaccination of the 5–9 years age group. The data from this study seem to confirm the circulation of B. pertussis in age groups not generally considered to be involved in the circulation of this pathogen, because of vaccination or natural immunity, and support previous reports in Italy and in other countries [36, 37].…”
Section: Discussionsupporting
confidence: 90%
“…In the age groups up to 19 years, the percentage of samples with high titres remained stable at 5–7·9%, reflecting natural boosting and limited vaccination of the 5–9 years age group. The data from this study seem to confirm the circulation of B. pertussis in age groups not generally considered to be involved in the circulation of this pathogen, because of vaccination or natural immunity, and support previous reports in Italy and in other countries [36, 37].…”
Section: Discussionsupporting
confidence: 90%
“…Infection does not confer life-long protection, and after vaccination antibody levels decrease even faster [4]. The large proportion of seropositive persons among adults vaccinated before age 40 and among unvaccinated adults over 40 suggests reinfection with B. pertussis, as has already been demonstrated in other studies [22,23].…”
Section: Discussionsupporting
confidence: 54%
“…An overview of epidemiology studies from Southern European countries is shown in Table 4 . This included studies from Cyprus [ 99 ], Greece [ 100 , 101 ], Italy [ 102 110 ], Portugal [ 85 ] and Spain [ 111 – 127 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…This included studies from Cyprus [ 99 ], Greece [ 100 , 101 ], Italy [ 102 110 ], Portugal [ 85 ] and Spain [ 111 – 127 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation